First, you expand the left hand side.
-8x + 12 = -8x + 5
And then add 8x to both sides.
12 = 5
At this point, you might be telling yourself, "HUH?!" Notice the x-variable disappeared, leaving you with a statement. What you have to do is determine the nature of this statement.
If the statement after eliminating the variable is false, then the answer is no solution.
If the statement after eliminating the variable is true, then the answer is all real numbers.
In this case, x has no solution.
However, suppose you had
4x + 8 = -2(-2x - 4)
That leaves us with
4x + 8 = 4x + 8
and
8 = 8
Note that this is a TRUE statement. So that means x can equal ANYTHING. That is, x is equal to all real numbers, meaning any number you plug into x will satisfy the equation.
2006-12-08 10:29:51
·
answer #1
·
answered by Puggy 7
·
2⤊
0⤋
Let's break this down. First, you have to multiply what's in the parentheses by what's outside them. So you can simplify this first by multiplying -4 by (2x - 3), which yields:
-8x + 12 = -8x + 5
Now you want to combine like terms (numbers with numbers, etc.), so you can subtract 5 from both sides and add 8x to both sides, which yields:
7 = 0x (12 - 5 = -8x + 8x)
Since any number times zero IS zero, x = 0.
Plug this back in to check your work:
-4 [2(0) - 3] = -8(0) + 5
-4 [0 - 3] = 0 + 5
0 + 12 = 0 + 5
12 = 5
Since 12 and 5 are definitely NOT equal, your answer has to be zero.
2006-12-08 18:36:13
·
answer #2
·
answered by ensign183 5
·
0⤊
0⤋
I think there is no solution because if you solve it out its be -8x+12 (because -4 time 2x is -8x and -4 (-3)=12)
SO its -8x +12=-8x + 5.
you can subtract 5 on each side so you then get
-8x + 7= -8x.
If you add 8x to -8x you get 0 so then you get
0=7
you cant solve that, so that's why i think there is no solution
2006-12-08 18:26:38
·
answer #3
·
answered by Tya 4
·
0⤊
0⤋
-4(2x - 3) = -8x + 5
- 8x + 12 = -8x +5
-8x + 8x = -12 +5
0x = -7
0 = - 7 ==> no solution (impossible to find a solution).
2006-12-08 19:20:08
·
answer #4
·
answered by frank 7
·
0⤊
0⤋
-4(2x-3)=-8x+5 I will explain, first you mulitply 2x and -3 by -4
-8x+12=-8x + 5 because they are in parenthesis. then you
+8x +8x subtract 8x from each side. Since what's left
12=5 is 12 and 5, they are not equal.
NO SOLUTION
2006-12-08 18:25:39
·
answer #5
·
answered by Anonymous
·
2⤊
0⤋
-4 (2x -3)= -8x + 5
-8x + 12 = -8x + 5
zero
>>`´<
2006-12-08 18:45:26
·
answer #6
·
answered by aeiou 7
·
0⤊
0⤋
Distributing the left hand side:
-4(2x - 3) = -8x + 12
So we have -8x + 12 = -8x + 5.
If we add 8x to both sides, we get 12 = 5, which is false.
There are no solutions.
2006-12-08 18:25:42
·
answer #7
·
answered by Adam 2
·
1⤊
0⤋
The 4 times the bracket
-8x + 12= -8X+5
then you solve for x, put the x on one side and the number on the other but this question is strange. The answer is 0.
2006-12-08 18:24:38
·
answer #8
·
answered by Webballs 6
·
0⤊
1⤋
-4 (2x -3)= -8x + 5 distribute -4
-8x+12=-8x+5 add 8x to each side
12=5
There is no solution to this problem.
2006-12-08 22:29:55
·
answer #9
·
answered by yupchagee 7
·
0⤊
0⤋
its a false statement -4x2x= -8x -4 x-3 =-12
so it says -8x+12=-8x+5 which is like saying 12=5, so its a false statement
i am assuming yall have been working on false statements lately
2006-12-08 18:25:39
·
answer #10
·
answered by ? 4
·
1⤊
0⤋